Hindering factors of the halal assurance system among restaurateurs and caterers in east Kalimantan Indonesia - Prabowo, Sulistyo (2016)
International halal business as well as awareness in halal products and services has been growing rapidly for the last few years. However, many industry players have not yet realized those huge potential concepts of halal business. Food service industries such as restaurants and caterings show less concern in putting priority on the issue of halal certification. It is hard to find research paper discussing halal management from Indonesian perspective. This study aims to explore various factors that hamper halal certification in food service industries in East Kalimantan, Indonesia. This study extends the use of qualitative research in halal management with the perspectives from many stakeholders in food service industries. A consecutive of qualitative data collection technique was employed to gain quality of research. In the beginning it used Nominal Group Technique (NGT), sharpens with in-depth interview and personal observations, and the findings were clarified by focus group discussion (FGD). Four categories of stakeholders participated in this study to represent certifying body, consumers, industry player and government. The use of combine qualitative method is an appropriate way to achieve the objective of this study efficiently. It provides a relatively new finding from Indonesian point of view. We can draw detailed list of factors hindering restaurant and food catering services in East Kalimantan Indonesia in obtaining halal certificate. These difficulties may result from both internal and external factors. Internal factors are: lack of knowledge and awareness, lack of outcome expectancy, management constraint, facility constraints, financial constraints, and type of product. External factors are: lack of dissemination information, lack of government's role, low of consumer awareness and demand, certification procedure, and limited suppliers of raw materials that meet the requirements, social and culture, constraints from the certifying body, less coordination and job description among the stakeholders, communication, the absence of consultancy, halal credentials, and halal data base availability. The results of this study reaffirm what was raised in the Roger’s theory of innovation adoption. Factors driving the adoption of a new system would not be met if the barriers still experienced by the organization or the industry. Considering the vast expanse of Indonesia and different level of development in each province, results of this study could not be generalized as Indonesia’s situation in general. However practical implication can be drawn. As halal certification in food service industry gains low interest from industries, this research presents hampering factors in various perspectives and offers some suggestions to overcome those issues accordingly.